100 cities, 5,000 ideas : where to go, when to go, what to see, what to do - Yogerst, Joseph R. (National Geographic, 2022)
"Discover the world's 100 best cities to explore - including amazing skylines, mouthwatering bites, and pure fun - in this smart and inspiring travel resource"--